Suppression of Residual Single-Photon Absorption Relative to Two-Photon Absorption in High Finesse Planar Microcavities - Donegan, John; Bradley, Louise (My University, 2008)
Suppression of residual single-photon absorption (SPA) relative to two-photon absorption (TPA) in a high finesse GaAs planar microcavity is explored. The TPA photocurrent becomes larger than the SPA photocurrent as long as the incident continuous-wave optical power exceeds 0.09 mW. An optical power of 5 mW would be required if the relative SPA suppression did not exist.
PUBLISHED
Keywords: Terms?Finesse; planar microcavity; single-photon absorption